(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
In the expediente we present the Urdimento Editorial Team, that is, the body of editors, associate editors, thematic dossier editors, editorial board, the editorial support team and the body the reviewers working in the issue of Urdimento.